2021
DOI: 10.1101/2021.02.18.21251776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid increase of SARS-CoV-2 seroprevalence during the 2020 pandemic year in the population of the city of Tirana, Albania

Abstract: Introduction: While the identification of anti SARS-CoV-2 antibodies has been used to measure the hidden circulation of the COVID-19 in communities, there are few publications on the dynamics of SARS-CoV-2 seroprevalence during both waves of 2020. This study provides original data about the change in proportion of individuals showing immune response to COVID-19 between beginning of July and end of December 2020. Methods: The study was conducted in two rounds, 27 June -3 July, and 21-28 December 2020, using tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
2
2
Order By: Relevance
“…They also help characterize the factors that contributed to immunity status in this understudied population. These data contrast with prior seroprevalence information we have reported from one year earlier in June-July 2020, and in December 2020, before the Alpha variant surge in Albania; we found using the same methodology seroprevalence rates of 7.5% and 48.2%, respectively [ 4 ]. A recent study conducted among health care workers in Albania between February and May 2021 has found a seroprevalence of 72% [ 5 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They also help characterize the factors that contributed to immunity status in this understudied population. These data contrast with prior seroprevalence information we have reported from one year earlier in June-July 2020, and in December 2020, before the Alpha variant surge in Albania; we found using the same methodology seroprevalence rates of 7.5% and 48.2%, respectively [ 4 ]. A recent study conducted among health care workers in Albania between February and May 2021 has found a seroprevalence of 72% [ 5 ].…”
Section: Discussioncontrasting
confidence: 99%
“…ly [4]. A recent study conducted among health care workers in Albania between February and May 2021 has found a seroprevalence of 72% [5].…”
Section: Discussionmentioning
confidence: 99%
“…This study of COVID-19 VE among HCWs in Albania, which -to the authors' knowledge -is the first COVID-19 VE study in an upper middleincome country in Europe, found moderate VE against PCR-confirmed COVID-19 among HCWs, most of whom had received two doses of BNT162b2 vaccine, during the Delta-predominant period. In contrast [20][21][22] , HCWs in this study had a high rate of prior infection only 1 year after the start of the pandemic, consistent with trends among HCWs in the Eastern European region, as well as high seroprevalence among the general population in Albania at this time [23] . In this population of previously infected HCWs, VE against COVID-19 was also moderate.…”
Section: Discussionsupporting
confidence: 81%
“…The enrolment profile of participants in our study offers unique challenges and opportunities. Over 70% of our study participants were seropositive for SARS-CoV-2 anti-spike antibodies on enrolment, a figure that is higher than the 48% seropositivity reported from a seroprevalence survey of the general population of Tirana, Albania during December 2020,23 which was nearly 2 months prior to the start of our study. Nearly all (98%) vaccinated participants had serology drawn within 4 days of their first vaccination, making it very unlikely that this seropositivity reflects a vaccine-induced antibody response.…”
Section: Discussioncontrasting
confidence: 57%